Analisis Prediksi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score Dan Grover Pada PT. MAG Tbk Pekanbaru - Shabrina, Salsabila; Ibrahim, Mariaty (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research was conducted to analyze and predict bankruptcy using the Altman Z-Score and Grover methods at PT. MAG Tbk Pekanbaru. Business failure (bankruptcy) is the thing that entrepreneurs fear most because many companies that have shaky foundations eventually dissolve themselves. Companies need to conduct financial analysis to identify early signs of bankruptcy. Much research has been conducted on bankruptcy detection tools, giving rise to various bankruptcy prediction models which are used as a tool to improve the condition of a company before the company experiences bankruptcy. Researchers chose 2 methods, namely Altman Z-score and Grover. Altman Z-score method to predict predictors with statistical methods by combining 4 financial ratios to calculate company failure. The Grover model is a model created by re-evaluating the Altman Z-Score model. The problem in this research is fluctuating profit/loss. The research method used is quantitative with financial ratios in the form of archival data which contains financial reports. The research results that have been processed based on the Altman Z-Score model and the Grover model show that the company is not in financial distress (Financial Distress) and the values between the Z-Score and Grover have similar criteria results because they use similar ratios.